METODE FAMĪ BISYAUQIN DI PONDOK PESANTREN PUTRI AL-BAQOROH LIRBOYO KEDIRI JAWA TIMUR DAN KONTRIBUSINYA DALAM MENJAGA AL-QUR’ĀN - Sabella, Dina; Noorhidayati, Salamah; Rahmawati, Emma (Al Hikmah: Jurnal Tarbiyah dan Ilmu Keguruan, 2022)
To realize the contribution in keeping the Qur'an, Muslims need an effort. One of the efforts in keeping the Qur'an is to apply the famÄ« bisyauqin method. FamÄ« bisyauqin method is a method of burying the Qur'Än within seven days that follows the method of radhiyalahu anhum companions by making hizb (grouping) the Qur'Än then featuring it on Thursday or Friday night. FamÄ« bisyauqin method has been implemented as a mandatory program in Pondok Pesantren Putri Al-Baqoroh Lirboyo Mojoroto, Kediri City, East Java. This method can also be done outside the cottage and can be applied by anyone. Before applying the method famÄ« bisyauqin need to be described the meaning of the method, its origin, and the application process in Pondok Pesantren Putri Al-Baqoroh Lirboyo Kediri. The purpose is to know the meaning and understanding contained in it and know how much contribution fami bisyauqin method in keeping the Qur'Än, then used historical approach with descriptive analytical explanation to get clear and detailed information. Keywords: History, Fami Bisyauqin Method, Contribution to Keeping the Quran.